2015
DOI: 10.1097/dcr.0000000000000266
|View full text |Cite
|
Sign up to set email alerts
|

American Joint Committee on Cancer and College of American Pathologists Regression Grade

Abstract: This is the first study to delineate American Joint Committee on Cancer/College of American Pathologists regression grade as an independent oncologic prognostic factor. This information can be used in discussions with patients who have rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 21 publications
1
107
1
4
Order By: Relevance
“…The AJCC/ CAP has recently proposed to use a three-tiered system based on Ryan et al original work (4). A recent report by Mace et al has definitively settled the prognostic influence of regression grade after CRT for rectal carcinoma in a large series of 538 patients (5). In this report, they have shown that regression is significantly associated to OS and also to local and distant recurrences.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The AJCC/ CAP has recently proposed to use a three-tiered system based on Ryan et al original work (4). A recent report by Mace et al has definitively settled the prognostic influence of regression grade after CRT for rectal carcinoma in a large series of 538 patients (5). In this report, they have shown that regression is significantly associated to OS and also to local and distant recurrences.…”
Section: Discussionmentioning
confidence: 58%
“…However, there is still discussion regarding the need to employ adjuvant therapy, so there has been much interest in determining prognostic factors that influence outcome of patients after CRT. Many systems to grade regression have been proposed and validated in different studies, but in recent years it has become clear that three tiered systems are more reproducible and give the same prognostic information as five-tiered ones (3)(4)(5). The AJCC/ CAP has recently proposed to use a three-tiered system based on Ryan et al original work (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, tumor regression grade (TRG) is a pathologic feature that should be reviewed in future studies and evaluated as a prognostic factor for outcomes, as it has received recent attention as a prognostic factor in LARC treated with nCRT. 34 Unfortunately, as TRG was added to the rectal cancer reporting criteria in the AJCC 7th edition (2010), and most of our patients were treated before 2010, we did not have sufficient cases to evaluate the prognostic impact of TRG. Finally, the 20 patients with pCR were not included in this study as our intention was to focus more directly on the prognostic impact of PNI on patients with residual tumor at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The pathologic tumor (T) and nodal (N) stages (ypT and ypN, respectively) of the tumor, histological grade, lymphovascular invasion, perineural invasion, tumor regression grade (TRG), and status of the circumferential, proximal, and distal resection margins were documented. The tumor response after CCRT was assessed according to the American Joint Committee on Cancer (AJCC) system as follows [18]: Grade 0, no residual cancer cells; Grade 1, single cell or small group of cancer cells (major regression); Grade 2, residual cancer with desmoplastic response (moderate regression); and Grade 3, minimal evidence of tumor response. A circumferential resection margin (CRM) of <1 mm was defined as an involved CRM [19].…”
Section: Methodsmentioning
confidence: 99%